Drug consumption in Colombia (2016)
This paper examines the evolution of drug use in Colombia over the past years. Our analysis, based on surveys from the Dirección Nacional de Estupefacientes, shows that drug consumption grew substantially between 1996 and 2013. The growth occurred for both genders, all ages, socioeconomic strata and types of occupation. The results also suggest that men of high socioeconomic strata who regularly consume alcohol and cigarettes and who are between 18 and 24 years of age are more likely to use drugs. Finally, the paper presents some indirect evidence that contradicts the alleged effects of the judgment of the Constitutional Court (Sentencia C-221 of May 1994) that decriminalized the personal dose on the consumption of drugs in Colombia.